Scaling social innovation: Ownership, documentation, infrastructuring elements and rehearsing new practices - Lone Malmborg (Artifact, 2023)
Today, co-designing for social innovation is explored in many western democracies to transform political agendas and develop sustainable societies. For social innovation to have a radical and wide-reaching impact on society, scaling is crucial. Scaling social innovation after ending a project requires a focus on making innovations sustainable in the long run and how they can foster organizational or institutional transformation. Despite increased interest in design for social innovation and scaling, little attention has been given to how the scaling of social innovation unfolds in practice over a longer period. A qualitative study was conducted following the continuation of a social innovation project called SeniorInteraction, which ended in 2012. Through interviews and field visits, we examined the attempts at scaling by different public and private partners and citizens after the project ended. The social innovation concept in question is an open exercise community in public parks for senior citizens supported by the local municipality. The research provides a deeper understanding of scaling in practice and identifies four important drivers for scaling social innovation: ownership, documentation, infrastructuring elements and rehearsing new practices. Additionally, we discuss challenges related to the way we understand and evaluate the scaling of social innovations.